Post-mastectomy radiotherapy after neodjuvant chemotherapy in breast cancer patients: A review. Issue 3 (March 2015) - Bernier, Jacques
Abstract Neoadjuvant chemotherapy followed by surgery is nowadays used in a significant number of patients presenting with locally advanced breast cancer. Most studies clearly demonstrate that, after mastectomy, local regional recurrences can be observed even when pathologic complete response is achieved after neoadjuvant chemotherapy, especially in patients with large size tumour and unfavourable pathologic factors. Retrospective studies remain the main source of information guiding the selective use of radiotherapy after neoadjuvant chemotherapy and mastectomy. This is one of the reasons why there are still many uncertainties regarding the indications of postmastectomy radiotherapy in this patient population. In addition, the extension of irradiation fields to peripheral lymphatics remains somewhat poorly defined in the literature. Finally combining the assessment of clinical and pathologic factors with the use of biomolecular assays should help oncologists determine with more accuracy which patients should receive post-mastectomy radiotherapy following neoadjuvant chemotherapy.